(untitled) (Bangladesh Journal of Zoology, 2015)
Some limnological parameters of water of Dhaka-Narayongonj-Demra (DND) dam canal were studied for one year period from May 2010 to April 2011. Sampling points were selected on the basis of human activities around the dam. The maximum water temperature was recorded in May 2010 (31.5 ± 0.2041°C) and minimum in December 2010 (18.3 ± 0.1925°C). Water transparency was highest in February 2011(38.1 ± 3.48 cm) and lowest in May 2010 (24.56 ± 2.722 cm). The maximum concentration of dissolved oxygen (DO) was found in winter month December 2010 (6.83 ± 0.4735 mg/l) and the minimum in summer month May 2010 (4.00 ± 0.2378 mg/l). The BOD was highest in August (34 ± 0.122 mg/l) and lowest in January (15 ± 0.274 mg/l). The highest amount of free carbon dioxide (free CO2) was recorded as 29.67 ± 4.4514 mg/l in January 2011 and the lowest 3.81 ± 0.8972 mg/l in August 2010. Maximum amount of hardness was found in December 2010 (271.20 ± 94.6597 mg/l) and minimum in September 2010 (196.20 ± 66.3963 mg/l) with a year round average of 229.51 ± 7.82 mg/l. pH was found fair (average 7.15 ± 0.08) during the study period. Maximum pH value 7.66 ± 0.14420 was recorded in the month of August while the minimum 6.74 ± 0.0574 in the month of May 2010. Although some water quality parameters of DND canal were found to be suitable for aquaculture but it was organically polluted. Further investigation on the heavy metal pollution is necessary before using the water and crops produced from DND canal for anthropological use. Bangladesh J. Zool. 41(2): 257-264, 2013